Fatty acid stable isotope signatures of molluscs exposed to finfish farming outputs - SM Colombo (Inter-Research, 2016)
Tracing the flow of nutrients from aquaculture operations to the surrounding biota is important for environmental monitoring and developing integrated aquaculture practices. A novel approach in this context, compound specific stable isotope analysis (CSIA) was used to trace fatty acid (FA) carbon in benthic invertebrates from multiple aquaculture sites in the Broughton Archipelago, British Columbia, Canada, up to 2500 m away from each site. We found that the carbon isotope ratios (δ13C) of certain FA in mussels and limpets were gradually 13C-enriched with increasing distance away from the site, suggesting that the farm contributed to more depleted isotopic signatures among organisms within the vicinity of the site. In mussels, the δ13C of 16:2n-4, 16:3n-4, 20:1n-9, 22:6n-3, saturated FA, the bacterial FA marker, and the overall weighted mean of FA became significantly more 13C-enriched with increasing distance from the farm (r2 > 0.28, p < 0.05). In limpets, the δ13C of 17:0, 18:4n-3, 20:4n-3 and the zooplankton FA marker became more enriched with distance away from the farm (r2 > 0.37, p < 0.05). The δ13C of mussels was also influenced by location of the farm, regardless of distance from the site. Non-indigenous isotopic signatures, as a result of feed inputs, physical properties of the farm location, and other anthropogenic influences, likely contributed to the depleted signature of mussels and limpets within the vicinity of the farm. This study was the first to use CSIA to determine the uptake and movement of organic nutrients from aquaculture outputs to the surrounding ecosystem.